Asymmetric nucleophilic fluorination under hydrogen bonding phase-transfer catalysis - Pupo, G; Ibba, F; Ascough, DMH; Vicini, AC; Ricci, P; Christensen, KE; Pfeifer, L; Morphy, JR; Brown, JM; Gouverneur, V; Paton, RS (American Association for the Advancement of Science, 2018)
Common anionic nucleophiles such as those derived from inorganic salts have not been used for enantioselective catalysis because of their insolubility. Here, we report that merging hydrogen bonding and phase-transfer catalysis provides an effective mode of activation for nucleophiles that are insoluble in organic solvents. This catalytic manifold relies on hydrogen bonding complexation to render nucleophiles soluble and reactive, while simultaneously inducing asymmetry in the ensuing transformation. We demonstrate the concept using a chiral bis-urea catalyst to form a tridentate hydrogen bonding complex with fluoride from its cesium salt, thereby enabling highly efficient enantioselective ring opening of episulfonium ion. This fluorination method is synthetically valuable considering the scarcity of alternative protocols and points the way to wider application of the catalytic approach with diverse anionic nucleophiles.